Effectiveness of the easing of monetary policy in the Japanese economy, incorporating energy prices - Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2014)
Japan has reached the limits of conventional macroeconomic policy. In order to overcome deflation and achieve sustainable economic growth, the Bank of Japan (BOJ) recently set an inflation target of 2% and implemented an aggressive monetary policy so this target could be achieved as soon as possible. Although prices started to rise after the BOJ implemented monetary easing, this may have been for other reasons, such as higher oil prices. Oil became expensive as a result of the depreciated Japanese yen and this was one of the main causes of the rise in inflation. This paper shows that quantitative easing may not have stimulated the Japanese economy either. Aggregate demand, which includes private investment, did not increase significantly in Japan with lower interest rates. Private investment displays this unconventional behavior because of uncertainty about the future and because Japan's population is aging. We believe that the remedy for Japan's economic policy is not to be found in monetary policy. The government needs to implement serious structural changes and growth strategies.
Keywords: E47; E52; Q41; Q43; 330; monetary policy; energy; oil prices; japanese economy